Irenaeus, Derrida and Hospitality: On the Eschatological Overcoming of Violence - Boersma, Hans (Modern theology, 2003)
God's hospitality or welcome of human beings into eternal life can be approached by means of Western (kataphatic) or Eastern (apophatic) strategies. I explore Derrida's understanding of 'pure hospitality', which contains parallels with apophatic theology. I then appeal to Irenaeus's eschatology, which exhibits a fruitful tension between kataphatic and apophatic elements, to provide a transcendent warrant for human hospitality. On the one hand, the Bishop's millenarian opposition to Gnosticism implies the continuation of the substance of creation in the eternal Kingdom. On the other hand, Irenaeus's emphasis on deification and visio Dei suggests a future of 'pure hospitality' and openness.